Presencia de Trypanosoma rangeli Tejera, 1920, en el Perú. I. El insecto vector, Rhodnius ecuadoriensis Lent & León, 1958 - Herrer, Aristides (1972)
Results of studies to determiné the geographic distribution of Rhodnius ecuadoriensis in the northern part of Peru revealed the presence of the insect in a single locality in each oE the Amazonian and the Pacific watersheds. Xerophitic vegetation is eharacteristic in these areas.All the different stages of the insect were found in human dwellings. In addition, eggs and nymphal instars were al so obtained in tree trunks and a pen where guineapigs were confined. This would indicate a versatile habit of the inseet which provides the opportunity to feed upon a wide variety of hosts under various environmental conditions.A very low infestation was observed during 1963-64. However, particular houses showed indications of possible higher infestations in previous years. Possible reasons for this phenomenon are discussed.